(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
This article analyses the order of the Court of Bologna of 31 December 2020 concerning the indirect collective discrimination committed by Deliveroo Italy S.r.l. against its riders through the management algorithm.